2022
DOI: 10.1038/s41598-022-13529-y
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and gene action for yield improvement in kenaf (Hibiscus cannabinus L.) under tropical conditions through diallel mating design

Abstract: Nine morphologically distinct kenaf genotypes were hybridized to produce 36 hybrids following a half diallel mating design. The combining ability and gene action of 15 yield and yield components were assessed in hybrids and their parents across two environments. Except for the mid diameter and plant height traits, there were highly significant differences (p ≤ 0.01) between the environments and the interaction of genotype and environment. Additive gene effects were considerable for the inheritance of these tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…On the other hand, the GCA/SCA for 100-seed weight was less than 1 (0.56), indicating that non-additive gene effects predominantly control this trait. Similar results were reported by others [32,35], where substantial differences between GCA and SCA allow the improvement of specific traits by selecting parents that pass on the desired traits to their offspring with additive genetic effects. Genetic analysis of fatty acid content in seed oil and studies on yield-forming traits have demonstrated significant differences between GCA and SCA in the F 1 generation, indicating the dominance of additive variability over non-additive variability [36].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the GCA/SCA for 100-seed weight was less than 1 (0.56), indicating that non-additive gene effects predominantly control this trait. Similar results were reported by others [32,35], where substantial differences between GCA and SCA allow the improvement of specific traits by selecting parents that pass on the desired traits to their offspring with additive genetic effects. Genetic analysis of fatty acid content in seed oil and studies on yield-forming traits have demonstrated significant differences between GCA and SCA in the F 1 generation, indicating the dominance of additive variability over non-additive variability [36].…”
Section: Discussionsupporting
confidence: 87%
“…However, results from this present study were confirmed by Ullah et al (2017), whose reported that the application of NPK resulted in greater growth and yield than the application of N, P, K, NP, NK, or PK. The results of growth parameters were also supported by other researchers, who reported that highly significant differences (p ≤ 0.01) between the environments and the interaction of genotype and environment were observed in kenaf genotypes on mid diameter and plant height traits (Al-Mamun et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…Adequate irrigation has the potential to increase the kenaf yield volume twofold [49]. Kenaf grows in places with a relative humidity ratio of 68 to 82% and temperatures varying from 22.6 to 30.3 • C [31]. According to Zhang et al [42], one of the most important factors influencing fibre production and quality in kenaf is the flowering stage, which is influenced by photoperiodism.…”
Section: Plant Growth Regulators (Pgrs)mentioning
confidence: 99%